Pendidikan Nilai dalam Pagelaran Wayang Kulit - Purwanto, Sigit (Taallum: Jurnal Pendidikan Islam, 2018)
Wayang kulit is a part of Indonesias local cultural form, which has existed and lasted from the time of the ancestors. Leather puppet performances are not only aimed for entertainment alone, but also contain noble values that can be manifested in every joint of life. Human image is manifested through playing the puppet. The art of wayang kulit develops as a quite effective means of planting the value and spreading of Islam. The value of education in the wayang kulit performances is based on logical, ethical, theological and aesthetic values. This paper aims to examine, explain and explore the educational value delivered through the wayang kulit performance.